Job stress and turnover intention: The mediating role of job satisfaction - Saputro, Dimas Eko (Universitas Ahmad Dahlan, 2024)
Purpose- Human resources are one of the important assets owned by every company. Its existence is needed in the operational process and determines the company's success in achieving its goals. Therefore, companies need to maintain competent employees. This study aims to analyze the level of turnover intention seen from job stress factors and mediated by job satisfaction. Design/Methodology/Approach- The object of this research is Matahari Department Store employees at Palu Grand Mall, Palu, Indonesia who are then given a questionnaire containing indicators of each variable. The number of samples in this study was 100 respondents, and data processing using Smart PLS software version 4. Findings- The results prove that only the first and second hypotheses are accepted, and job stress has a positive effect on turnover intention and job satisfaction. Job satisfaction has a negative effect on turnover intention, but it is not significant. The mediation hypothesis in this study was also rejected, so job satisfaction does not mediate the impact of job stress on turnover intention. Research limitations/implications- This study is limited to employees of the Matahari Department Store in Palu Grand Mall, Palu, Indonesia. Therefore, the results can not be generalized or describe the condition of all employees of Matahari Department Store. However, the results of this study can be used as evaluation material by the management of Matahari Department Store in order to reduce the number of turnover intentions. Originality/value- This study uses employees of the Matahari Department Store in Palu Grand Mall, Palu, Indonesia, as the research object. Similar research has been done with similar objects but in different locations. In addition, this study uses the mediating variable of job satisfaction.